Global Compact on Refugees: Dilemma Between National Security and Human Security - Agusman, Hardy; Sundrijo, Dwi Ardhanariswari (Interdisciplinary Social Studies, 2023)
Background: The refugee crisis have been an international concern as it is considered a multidimensional threat to security issues, both national and human security. States increased the level of protection that aims ‘to maintain and to protect’ their borders on behalf of sovereignty. On the other hand, refugees have the right ‘to seek and to enjoy’ asylum from persecution in other countries. In this context, refugee crisis implies the paradigm clash between national security and human security. The Global Compact on Refugees (GCR) is presented as the product of a “States Plus” approach to multilateralism that brought together several states, other stakeholders, and refugees to solve the dilemma above with the principle of burden and responsibility-sharing. Aim: This article analyzes the legal mechanism that impacts the financial resources and fulfilment of the GCR objectives. Method: The researcher combined a qualitative approach with a methodology for conducting a literature review. The majority of the articles and other sources used to compile the study's data were books and academic publications that examined relevant subjects. Findings: Previously, refugee handling in the global refugee regime (1951 Convention and 1967 Protocol) tended to be state-centred. In contrast, GCR tends to be people-centred and comes from the refugee crisis realities (bottom-up). However, from the implementation aspect, there is a significant gap between the targets made in the Global Refugee Forum and its achievements. This discourse was dominated by a traditional state security perspective, while the humanitarian language emerged only in design framework of GCR.